The clinical benefit of hyperthermia in pancreatic cancer: a systematic review. (3rd October 2018) - van der Horst, Astrid; Versteijne, Eva; Besselink, Marc G. H.; Daams, Joost G.; Bulle, Esther B.; Bijlsma, Maarten F.; Wilmink, Johanna W.; van Delden, Otto M.; van Hooft, Jeanin E.; Franken, Nicolaas A. P.; van Laarhoven, Hanneke W. M.; Crezee, Johannes; et al.
Abstract: Objective: In pancreatic cancer, which is therapy resistant due to its hypoxic microenvironment, hyperthermia may enhance the effect of radio(chemo)therapy. The aim of this systematic review is to investigate the validity of the hypothesis that hyperthermia added to radiotherapy and/or chemotherapy improves treatment outcome for pancreatic cancer patients. Methods and materials: We searched MEDLINE and Embase, supplemented by handsearching, for clinical studies involving hyperthermia in pancreatic cancer patients. The quality of studies was evaluated using the Oxford Centre for Evidence-Based Medicine levels of evidence. Primary outcome was treatment efficacy; we calculated overall response rate and the weighted estimate of the population median overall survival ( mp ) and compared these between hyperthermia and control cohorts. Results: Overall, 14 studies were included, with 395 patients with locally advanced and/or metastatic pancreatic cancer of whom 248 received hyperthermia. Patients were treated with regional ( n  = 189), intraoperative ( n  = 39) or whole-body hyperthermia ( n  = 20), combined with chemotherapy, radiotherapy or both. Quality of the studies was low, with level of evidence 3 (five studies) and 4. The six studies including a control group showed a longer mp in the hyperthermia groups than in the control groups (11.7 vs. 5.6 months). Overall response rate, reported in three studies with a control group, was also better for the hyperthermia groups (43.9% vs. 35.3%). Conclusions: Hyperthermia, when added to chemotherapy and/or radiotherapy, may positively affect treatment outcome for patients with pancreatic cancer. However, the quality of the reviewed studies was limited and future randomised controlled trials are needed to establish efficacy.